Are Organizations Accountable? Disconnect between Gender and Sanitation in Bangladesh. (March 2018) - Mannan, Fouzia
Deep-rooted gender inequalities exist in organizations responsible for provisioning sanitation facilities in Bangladesh with regard to organizational culture, financial status and power axis within and beyond the organizations. There are huge gaps between these organizations as these have differential gender-sensitive policies or even lack proper understanding of gender. Without having a gender-sensitive leadership within organizations, sanitation issues continue to have a male-dominated bias. Given the patriarchal organizational culture and mindset in Bangladesh, serious rethinking is needed to bring about a gender-sensitive sanitation policy. This article aims to investigate gender issues in sanitation through qualitative analysis of select sanitation and water-implementing organizations in Dhaka and explore how they understand, interpret and practice 'gender'.